Corrigendum to: Promotion Strategy by Palu City Government to Pulling Investors Interest in Palu Special Economic Zone - Redaksi Jurnal ASPIKOM (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
After the publication of the article titled